Is polytrauma really just a simple accident? Recurrent characteristic of polytrauma - Cong Zhang; Peidong Zhang; Deng Chen; Qian Wan; Gang Yin; Yang Liu; Jialiu Luo; Shunyao Chen; Zhiqiang Lin; Shuaipeng Gu; Hui Li; Liming Dong; et al. (BMC, 2024)
Abstract Background Polytrauma was defined as a severe traumatic injury and believed that it was a sudden and unpredictable incident. Is polytrauma really just a simple accident? In order to comprehensively answer this question, the study sought to determine the frequency and specific risk factors associated with polytrauma recidivism, while also comparing the initial and subsequent injury events among recidivists. Methods A multicenter, retrospective cohort study was conducted at four Advanced Trauma Centers' emergency surgery or traumatic intensive care units (TICUs) between August 2020 and July 2023. A total of 2490 consecutive trauma patients who met the criteria consecutively were recruited and analyzed in the study. Risk factors for recurrent polytrauma were identified through the use of logistic regression analysis. A nomogram was created using the results from a multivariate logistic regression analysis and the rms package in R. Results In polytrauma, the rate of recidivism was 44.6% (672/1507), then recidivists were predominantly male (80.4%) and frequently within the 45 to 54 year-old age range (51.3%). Recidivists in polytrauma patients overall had a median time to reinjury of 27 months, as measured by the interquartile range (IQR). The polytrauma patients in the recent traumatic event were often more severe than that in the initial event, as patients had higher ISS scores and lower GCS scores (P < 0.01). Moreover, polytrauma recidivism were associated with poorer prognosis and increased healthcare costs. Polytrauma patients with the specific characteristics were found to have a higher likelihood of experiencing a subsequent recurrence, including being male (OR = 3.82,95% CI: 2.21-6.83), aged 45-54 years old (OR = 2.62,95% CI: 2.13-6.32),experiencing sleep deprivation (OR = 2.38,95% CI: 1.32-4.25), working in construction (OR = 2.72,95% CI: 1.44-5.42), working as delivery staff (OR = 3.65,95% CI: 1.51-7.96) and being involved in an electric bicycle collision (OR = 2.85,95% CI: 1.31-5.64). Conclusion Polytrauma recidivism is associated with a high recurrence rate, poorer clinical outcomes, and elevated healthcare costs. Key predictive markers for recidivism include being male, aged 45-54 years, experiencing sleep deprivation, employment in construction or delivery roles, and involvement in electric bicycle collisions. These findings highlight polytrauma recidivists as a critical target for primary prevention efforts. Public health strategies should prioritize tailored interventions to reduce recidivism, aiming to mitigate morbidity, mortality, and associated healthcare burdens in this high-risk population.